Hypothalamic Control of Systemic Glucose Homeostasis: The Pancreas Connection. (August 2018) - Pozo, Macarena; Claret, Marc
Abstract : Maintenance of glucose homeostasis is mandatory for organismal survival. It is accomplished by complex and coordinated interplay between glucose detection mechanisms and multiple effector systems. The brain, in particular homeostatic regions such as the hypothalamus, plays a crucial role in orchestrating such a highly integral response. We review here current understanding of how the hypothalamus senses glucose availability and participates in systemic glucose homeostasis. We provide an update of the relevant signaling pathways and neuronal subsets involved, as well as of the mechanisms modulating metabolic processes in peripheral tissues such as liver, skeletal muscle, fat, and especially the pancreas. We also discuss the relevance of these networks in human biology and prevalent metabolic conditions such as diabetes and obesity. Highlights: Fluctuations in hormones and glucose levels are sensed by specific subsets of hypothalamic neurons as a proxy for overall metabolic status. The hypothalamus integrates this information and accordingly modulates effector mechanisms to maintain metabolic homeostasis. Glucose homeostasis is achieved by coordinating hepatic glucose production, muscle and fat glucose uptake, as well as endocrine pancreas function. The ventromedial hypothalamus is a crucial nexus in the initiation of the glucose counter-regulatory response which is partially mediated via glucagon release by the pancreas. The arcuate nucleus of the hypothalamus is preferentially implicated in fine-tuning insulin release.